Use of shrimp farming waste in the production of biomaterials for sustainable agriculture and mitigation of environmental damage - Lima Bomfim, Jôse Raymara Alves; da Costa Cunha, Graziele; Botero, Wander Gustavo; Romão, Luciane Pimenta Cruz [UNESP] (Wiley, 2023)
Background: Due to the environmental degradation caused by shrimp farming in Brazilian mangrove ecosystems, it is of great importance to develop techniques capable of inserting waste into the production chain, strengthening the premise of sustainable shrimp farming development due to its economic and social impact. In this work, solid residues from shrimp farming were used as a slow-release fertilizer (SRF) in formulations that also contain chitosan, montmorillonite, and urea. Results: Fertilizer granules produced without (FERT A) and with additional layers (FERT B) were characterized by elemental analysis (Carbon, Hydrogen, Nitrogen), obtaining values of 14.4%–18.4% for carbon, 5.6%–6.9% for hydrogen, and 12.3%–19.3% for nitrogen. The fertilizers had low C/N ratios of around 1.0–1.50, compared to a value of 0.87 for urea, the nitrogen fertilizer most widely used in Brazilian agriculture. Release tests in water showed the same release pattern in the first 5 min for FERT A and FERT B, with <10% urea release. After 30 min, the release from the fertilizers progressively increased, reaching >60% after 1 day and a maximum of 95%–97% after 15 days. In the first 3 days of incubation in the soil, the releases of nitrogen from FERT A, FERT B, and conventional urea presented different patterns, with values of 32%, 10%, and 90%, respectively. After incubation for 25 days, FERT A and FERT B presented nitrogen releases lower than 78%, confirming the slow release of the nutrient from these fertilizers. Degradation experiments showed that the fertilizers were biodegradable in the soil, with degradation exceeding 60% after 30 days, indicating that they could be applied to the soil without leaving residues. Conclusions: The fertilizer granules produced are SRFs that have the potential to increase the efficiency of nitrogen fertilization, reducing the frequency of applications and minimizing nitrogen losses in the soil. In addition, they enable the reuse of shrimp farming waste, producing a new material of agricultural interest.
Keywords: mangroves; montmorillonite; shrimp farming; slow-release fertilizer; soil; urea